Anemia decreases quality of life of the elderly in Jakarta - Meiyanti, Meiyanti; Kalumpiu, Joice Viladelvia; Mulia, Julius I (Universa Medicina, 2009)
Anemia is a very common disorder both in clinical practice and in the community. The recent rise in the population of the elderly has become the focus of attention in developing countries, because of the increasing longevity of the elderly, whilst the prevalence of anemia increases with age. The objective of this study was to determine the prevalence of anemia and its association with the quality of life in the elderly. A cross-sectional study was conducted from April to June 2008, located in the Mampang Prapatan district, South Jakarta. A total of 298 elderly persons participated in this study, comprising 109 (36.6%) males and 189 (63.4%) females. Anemia was measured by the parameters of hemoglobin and quality of life was assessed by the WHOQOL-BREF instrument, a short version of the WHOQOL-100 instrument. The results of the study showed the prevalence of anemia to be 26.2%, with a higher prevalence rate in females compared with males. The quality of life in the physical, psychological, social and environmental domains differed significantly with decreasing hemoglobin levels, whereas the physical and mental quality of life declined significantly with age. Anemia is thus indicative of a reduction in the quality of life of the elderly.